Exploring automatic approach-avoidance tendencies: the impact of self-relevant social feedback on behavior - Kim, Jinhee; Lee, Meeseung; Chae, Jihwan; Lim, Gahyun; Kim, Minyoung; Kim, Hackjin (Frontiers in Psychology, 2025)
Previous studies have reported automatic approach-avoidance tendencies toward various stimuli, such as words, facial expressions, and images in the appetitive or aversive valence domain. This work investigates whether self-relevant evaluative feedback affects these behavioral tendencies using a touchscreen-based approach and avoidance task, in which participants responded to two-colored fish icons either by pulling toward or by pushing away from themselves. Evaluative feedback on participants' personality traits, provided by the fish, served as a task-irrelevant feature. A pronounced valence-congruence effect for positive feedback relative to negative feedback was observed. Interestingly, higher social desirability ratings of social feedback were associated with faster reaction times for approach trials and slower reaction times for avoidance trials. Personality traits were linked to approach tendencies: higher fear of negative evaluation scores predicted a slower approach for both positive and negative feedback compared to neutral feedback. This study demonstrates automatic approach and avoidance tendencies toward self-relevant social feedback, indicating a behavioral predisposition that may be automatically triggered by such feedback. Additionally, this study lays the groundwork for developing touchscreen-based approach-avoidance tasks for measuring individual differences in sensitivity to social feedback and the strength of behavioral predispositions.